Privatisation of public services in the EU: an attack on social cohesion and democracy. (1st October 2008) - ,
Abstract : In the past, universal access to essential public services served as an important mechanism for generating a good relationship between the market, social cohesion and democracy in many European countries. But, with the growing dominance of the mode of ''negative integration'' across the continent, citizens are being reconstituted as consumers and small shareholders. Meanwhile, privatisation of public services steamrolls the results of the ''decommodification of wage labour'' achieved in the short ''social democratic century''. Drawing on the results of the EU-funded Co-ordination Action PRESOM (Privatisation and the European Social Model) this paper argues that in the long run these developments might affect the democratic functioning of the Union and the integration process as a whole. Further information about PRESOM can be found onhttp://www.presom.eu .